Abmas-Td Pengolahan Nilai Mahasiswa Dan Pelaporan Keuangan Dengan Microsoft Excel - Darsini Darsini; Ainur Komariah; Budi Wibowo (Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
Universitas Veteran Bangun Nusantara Sukoharjo consists of 20 study programs spread across 6 faculties with 162 lecturers. At the end of each semester, all lecturers have the task of reporting the grades obtained by students to the study program. In addition to assessing each lecturer in carrying out activities and having to report the use of funds. To assist lecturers in reporting assessments and compiling reports on the use of funds or financial reports, this computer training activity is important to be carried out to help improve the skills of lecturers and employees in operating the Microsoft Ecxel program. The method used in this community service is to provide training material and directly practice in a computer laboratory. From the provision of material, it was then carried out training on questions and evaluation. Evaluation is carried out to determine the increase in knowledge and skills of the Microsoft Ecxel program. Microsoft ecxel is a program that can be used to process data quickly, precisely and accurately according to user requests. The result of this service activity is an increase in the skills of lecturers and employees in computer operation and certificates for training participants. Based on the results of the pre test and post test, there was an increase of 48.94% after computer training